STUDI EKSPLORASI FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DI KABUPATEN JEPARA - Senowarsito Senowarsito; Arri Handayani; Iin Purnamasari; Achmad Bukhori (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The purpose of this research is to analyze the factors that cause dropping out of school in Jepara Regency.The research method used is qualitative with a descriptive approach. Collecting data using questionnaires, in-depth interviews, documentation, and FGDs related to the causes of dropping out of school. The research respondents consisted of school dropouts, parents, and teachers from 14 sub-districts in Jepara Regency. qualitative descriptive research procedures in a naturalistic manner. The data source was selected by purposive sampling as a sample determination. Primary data was obtained in verbal form, the words revealed based on filling out a questionnaire related to the research topic. Research instruments in the form of open and closed questionnaires are used to reveal the factors that cause children to drop out of school. This research was conducted through four stages, namely orientation, exploration, member check and reporting stage. Data collection techniques used questionnaires, in-depth interviews, documentation and FGDs related to the factors that cause children to drop out of school. Data analysis was carried out through triangulation, both source and technique triangulation.The results of the study found that the internal conditions of individuals, such as motivation and external factors from family and environment were the main factors in the dropout rate. If the child is not motivated, is not supported by the family, and is not supported by the environment, the chances of students dropping out of school will be higher. In this case, when schools have tried to persuade children to attend school but without internal motivation and support from parents, the chances of children dropping out of school are still great.